Tingkat Kesiapsiagaan Siswa Terhadap Bencana Banjir Di SMA Negeri 1 Tawangsari Kabupaten Sukoharjo - Asror, Lail Nur; , Dr. Tjipto Subadi, M.Si (2015)
Purpose of the research is to know preparedness level of students for flood disaster in SMA Negeri (Public High School) 1 Tawangsari. The research is quantitative one. Population of the research is all 124 students of Social Science Classrooms with classroom XI of the school as a population target. Sample of the research is 56 students. The sample was taken by using a random sampling technique. Data of the research was collected by using Guttman and Interval scales, observation and documentation. Validity and reliability tests as requirements of analytical test were completed. Results of the research indicated that preparedness level for flood disaster of the students of class XI Social Science can be categorized as low. It was proved by results of data analysis showing score 665 on preparedness level for flood disaster obtained by the students